2016
DOI: 10.1038/nchembio.2239
|View full text |Cite
|
Sign up to set email alerts
|

ACSL4 dictates ferroptosis sensitivity by shaping cellular lipid composition

Abstract: Ferroptosis is a form of regulated necrotic cell death controlled by glutathione peroxidase 4 (GPX4). At present, mechanisms that could predict sensitivity and/or resistance and that may be exploited to modulate this form of cell death are needed. We applied two independent approaches, a genome-wide CRISPR-based genetic screen and microarray analysis of ferroptosis-resistant cell lines to uncover acyl-CoA synthetase long-chain family member 4 (Acsl4) as an essential component for ferroptosis execution. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

62
2,098
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,630 publications
(2,365 citation statements)
references
References 52 publications
62
2,098
1
4
Order By: Relevance
“…The evidence suggests that ACSL4 is not a critical enzyme to increase cell growth and viability in ER-negative breast cancer. On the other hand, a recent study demonstrates that ACSL4-silencing breast cancer cells resist ferroptosis and the w6 fatty acid acids are enriched in cellular membrane under ferroptosis stimulation (48). The mammalian target of rapamycin (mTOR) signaling pathway is regulated by ACSL4 in breast cancer cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence suggests that ACSL4 is not a critical enzyme to increase cell growth and viability in ER-negative breast cancer. On the other hand, a recent study demonstrates that ACSL4-silencing breast cancer cells resist ferroptosis and the w6 fatty acid acids are enriched in cellular membrane under ferroptosis stimulation (48). The mammalian target of rapamycin (mTOR) signaling pathway is regulated by ACSL4 in breast cancer cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…Free PUFAs are substrates for synthesis of lipid signaling mediators, yet they must be esterified into membrane phospholipids and undergo oxidation to become ferroptotic signals (Kagan et al, 2017). Lipidomic studies suggest that phosphatidylethanolamines (PEs) containing arachidonic acid (C20:4) or its elongation product, adrenic acid (C22:4), are key phospholipids that undergo oxidation and drive cells towards ferroptotic death (Doll et al, 2017; Kagan et al, 2017). Therefore, formation of coenzyme-A-derivatives of these PUFAs and their insertion into phospholipids are necessary for the production of ferroptotic death signals.…”
Section: The Biochemical Control Of Ferroptosismentioning
confidence: 99%
“…Loss of these gene products depletes the substrates for lipid peroxidation and increases resistance to ferroptosis (Dixon et al, 2015; Doll et al, 2017; Kagan et al, 2017; Yuan et al, 2016b). Conversely, cells that are supplemented with arachidonic acid or other PUFAs are sensitized to ferroptosis (Yang et al, 2016).…”
Section: The Biochemical Control Of Ferroptosismentioning
confidence: 99%
“…Also, 12-HETE-d8 is not incorporated into platelet PE during the timescale of agonist-stimulated 12-HETE-PE generation, indicating that exogenous and endogenously generated eicosanoids are somehow sensed differently and suggesting that cell compartmentalization is an important factor (13). Last, two recent studies by Kagan, Conrad, and coworkers (23,24) showed that ACLS4 shapes lipid composition, including formation of oxidized arachidonate and adrenic acid-PEs by lipoxygenase, during a cell death process called ferroptosis.…”
mentioning
confidence: 99%